ANALYSIS OF INVESTMENT PORTFOLIO PERFORMANCE INDICATORS (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes investment portfolio performance indicators, particularly Sharpe, Treynor, Sortino, Jensen’s Alpha, and Modigliani–Miller indicators, calculated based on a portfolio formed from 15 stocks. Based on the obtained results, scientific conclusions are presented regarding how effective the portfolio is for investors.
Keywords: Portfolio performance, Sharpe ratio, Treynor ratio, Jensen alpha coefficient, Sortino ratio, Modigliani–Miller, ROA, ROE, P/B, P/E, D/E indicators, beta coefficient.